Rare Metastasis to the Submandibular Gland in Oral Squamous Cell Carcinoma - Zhou, Ping; Chen, Jing-Xin; Zhou, Yuan; Lian, Chen-Lu; Yan, Bing; Wu, San-Gang (Frontiers in Oncology, 2021)
Purpose: In the current recommendation of neck dissection in oral squamous cell carcinoma (OSCC), the submandibular gland (SMG) should be also removed. This study aimed to investigate the incidence and the patterns of SMG involvement in OSCC patients. Methods: Patients initially diagnosed with OSCC between January 2018 and October 2020 were included. The distribution of lymph nodes metastasis in level IB was analyzed. Results: We included 145 patients who underwent primary surgery and neck dissection in this study. All patients had level IB lymph node dissection and simultaneous removal of the SMG. Of these patients, only one patient (0.7%) had involvement in SMG by directly infiltrating from the primary tumor. A total of 18 positive lymph nodes were found in level IB in 16 patients, and no positive lymph nodes were located in the SMG. There were 6 lymph nodes located in the lateral part of the SMG and 12 lymph nodes located in the anterior of the SMG. Patients with tumors located in the buccal mucosa and N3 stage were the independent predictive factors associated with level IB nodal metastasis. Conclusion: Involvement of SMG in OSCC is quite rare. Preservation of the SMG during neck dissection in selected patients with OSCC seems to be feasible and oncologically safe